Strengthening digital literacy in helping to learn during a pandemic - Luthfi Nur Hakim; Henri Nusantara (Universitas Pendidikan Indonesia, 2023)
The implementation of distance learning has increased the frequency of using digital technology by students and teachers. Expanding the use of digital technology needs to be balanced with efforts to increase students' and teachers' understanding of digital literacy. This article attempts to discuss how the results of strengthening digital literacy are carried out in community service programs. Socialization of the importance of digital literacy was also carried out to the school community as part of the Real Work Lecture activities conducted at SDN 158 Babakan Sari Babakan Surabaya. The method used in this research is strengthening digital literacy for students, teachers, and parents. Service activities include the socialization of digital literacy by teaching in class; outreach to students, teachers, and parents through digital media such as infographics, YouTube videos, and news articles. Spontaneous discussions with teachers regarding digital literacy. Introduction to several applications and digital media that can be used in distance learning. Abstrak Diberlakukannya pembelajaran jarak jauh membuat frekuensi penggunaan teknologi digital oleh siswa dan guru menjadi meningkat. Peningkatan penggunaan teknologi digital ini perlu diimbangi dengan upaya peningkatan pemahaman siswa dan guru terhadap literasi digital. Artikel ini berusaha untuk membahas bagaimana hasil penguatan literasi digital yang dilaksanakan pada program pengabdian kepada masyarakat. Dan juga dilakukan sosialisasi pentingnya literasi digital kepada masyarakat sekolah sebagai bagian dari kegiatan Kuliah Kerja Nyata yang dilakukan di SDN 158 Babakan Sari Babakan Surabaya. Metode yang digunakan dalam penelitian ini adalah penguatan literasi digital bagi siswa, guru, dan orang tua. Bentuk kegiatan pengabdian yang dilakukan, di antaranya sosialisasi literasi digital dengan mengajar di kelas; sosialisasi kepada siswa, guru, dan orang tua melalui media digital seperti infografis, video youtube, dan artikel berita. Diskusi spontan dengan guru terkait literasi digital. Pengenalan beberapa aplikasi dan media digital yang dapat digunakan dalam proses pembelajaran jarak jauh. Kata Kunci: KKN UPI; pembelajaran jarak jauh; penguatan literasi digital; teknologi digital